2019
DOI: 10.3389/fneur.2019.01006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Functional Connectivity in Cognitive Control Network, Default Mode Network, and Visual Attention Network in Internet Addiction: A Resting-State fMRI Study

Abstract: Internet addiction (IA) has become a global mental and social problem, which may lead to a series of psychiatric symptoms including uncontrolled use of internet, and lack of concentration. However, the exact pathophysiology of IA remains unclear. Most of functional connectivity studies were based on pre-selected regions of interest (ROI), which could not provide a comprehensive picture of the communication abnormalities in IA, and might lead to limited or bias observations. Using local functional connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 98 publications
1
32
0
Order By: Relevance
“…Thus, all analyses in our study were based on these 57 subjects (27 IA subjects and 30 HCs). Thirteen of the 27 IA subjects were included in our prior article investigating the abnormal functional connectivity density in IA [28] and further consented to participate in the present study to explore the modulation effect of acupuncture on IA. Table 1, no significant intergroup difference was observed in age, gender, or years of education at baseline (p > 0:05).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, all analyses in our study were based on these 57 subjects (27 IA subjects and 30 HCs). Thirteen of the 27 IA subjects were included in our prior article investigating the abnormal functional connectivity density in IA [28] and further consented to participate in the present study to explore the modulation effect of acupuncture on IA. Table 1, no significant intergroup difference was observed in age, gender, or years of education at baseline (p > 0:05).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the associations between the classifying features and the severity of symptoms, voxel-based correlation analyses (48) were conducted between the meaningful classifying features and the duration/baseline MMDs/baseline VAS scores in patients with MWoA. The statistical significance threshold of the correlation was set to p < 0.05 (uncorrected) and the threshold of cluster size was set to 20 contiguous voxels.…”
Section: Study 1: Pattern Classification Of Patients With Mwoa and Hsmentioning
confidence: 99%
“…In a longitudinal fMRI study, the FC of the putamen in individuals with IA was also found to be significantly correlated with the online time per day, suggesting that the habitual use of the internet was related to hyperactive impulsive habit system in the brain (Lee et al, 2021). Using functional connectivity density (FCD) analysis, a novel method that overcomes the bias of FC produced by the preselection of ROIs, to analyze whole-brain functional communication, we further found altered dorsolateral prefrontal cortex (DLPFC) function in our prior study (Wang et al, 2019), representing the defective reflecting system in IA. These fMRI studies have provided us with the potential neuropathologic mechanism underlying IA; however, the average differences between groups are insufficient in guiding individual clinical practice directly.…”
Section: Introductionmentioning
confidence: 80%
“…Thus, the final dataset included data obtained from 27 individuals with IA and 30 HCs. Fifteen of 27 individuals with IA had participated in our former fMRI study detecting functional abnormalities in IA (Wang et al, 2019) and further consented to take part in the present CBT study. Each individual with IA met the diagnostic criteria for IA (assessed by the Internet Addiction Questionnaire), while all the demographically matched HCs did not meet the criteria for IA.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation